The alcohol policy environment, enforcement and consumption in the United States. (30th September 2015) - Erickson, Darin J.; Lenk, Kathleen M.; Toomey, Traci L.; Nelson, Toben F.; Jones‐Webb, Rhonda
Abstract: Introduction and Aims: Many studies of alcohol policies examine the presence or absence of a single policy without considering policy strength or enforcement. We developed measures for the strength of 18 policies (from Alcohol Policy Information System) and levels of enforcement of those policies for the 50 US states, and examined their associations with alcohol consumption. Design and Methods: We grouped policies into four domains (underage alcohol use, provision of alcohol to underage, alcohol serving, general availability) and used latent class analysis to assign states to one of four classes based on the configuration of policies—weak except serving policies (6 states), average (29 states), strong for underage use (11 states) and strong policies overall (4 states). We surveyed 1082 local enforcement agencies regarding alcohol enforcement across five domains. We used multilevel latent class analysis to assign states to classes in each domain and assigned each state to an overall low (15 states), moderate (19 states) or high (16 states) enforcement group. Consumption outcomes (past month, binge and heavy) came from the Behavioral Risk Factor Surveillance System. Results: Regression models show inverse associations between alcohol consumption and policy class, with past month alcohol consumption at 54% in the weakest policy class and 34% in the strongest. In adjusted models, the strong underage use policy class was consistently associated with lower consumption. Enforcement group did not affect the policy class and consumption associations. Discussion and Conclusions: Results suggest strong alcohol policies, particularly underage use policies, may help to reduce alcohol consumption and related consequences. [Erickson DJ, Lenk KM, Toomey TL, Nelson TF, Jones‐Webb R. The alcohol policy environment, enforcement, and consumption in the United States. Drug Alcohol Rev 2015;●●:●●–●●]